Combined Scheduling and Control - Logan Beal (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Scheduling and control are typically viewed as separate applications because of historical factors such as limited computing resources. Now that algorithms and computing resources have advanced, there are new efforts to have short-term decisions (control) interact or merge with longer-term decisions (scheduling). A new generation of numerical optimization methods are evolving to capture additional benefits and unify the approach to manufacturing process automation. This special issue is a collection of some of the latest advancements in scheduling and control for both batch and continuous processes. It contains developments with multi-scale problem formulation, software for the new class of problems, and a survey of the strengths and weaknesses of successive levels of integration.